Sponge Takeover from End-Permian Mass Extinction to Early Induan Time: Records in Central Iran Microbial Buildups - Baud, Aymon; Richoz, Sylvain; Brandner, Rainer; Krystyn, Leopold; Heindel, Katrin; Mohtat, Tayebeh; Mohtat-Aghai, Parvin; Horacek, Micha (Frontiers in Earth Science, 2021)
The end-Permian mass extinction (EPME) is marked by a major crisis in Phanerozoic carbonate systems that likely reflected a large-scale change in ocean chemistry and have repercussions during its aftermath. At the basal Triassic distal carbonate ramp of Central Iran, unusual non-skeletal carbonates have been deposited, so-called "crystal layers" or "carbonate crusts". We show here that those carbonates are sponge microbial buildups (SMB) built by digitate stromatolite columns, small aragonitic overgrowth and sponges. They are very similar to the SMBs recently described in South Armenia. All the SMB cropping out along the Cimmerian margin of the Neotethys are interpreted as (a) short bio-event(s) and belong to a Time Specific Facies (TSF). In this study, we mainly focus on two well-known Permian-Triassic boundary and post extinction localities: the Kuh e Hambast section east of Abadeh city and the more distal Shahreza section near Isfahan. In both sections, the extinction horizon belongs to the top of the latest Permian Paratirolites limestone. At Kuh e Hambast, the overlying so-called “boundary clay” is conformably overlain by basal Triassic dark lime mudstone containing four successive levels of decimeter to meter scale elongated to cup- shaped mounds made of branching columnar stromatolites. Sponge fibers, possible keratose demosponge, are widely present in the lime mudstone matrix. At the Shahreza section, above the extinction level, five SMB levels are present overlying each other in the lower 20 m of the basal Triassic platy limestone. The first, latest Permian in age, is made of micro-laminated calcite crystal bundles interpreted as digitate stromatolite, with calcite-cemented fibrous interspaces in a micritic clump. The fibers and spicules in micritic matrix are considered as sponge fossils. Some overlying SMB consist of thrombolite domes, and other buildups of more complex structure, show again micro-laminated calcite crystal bundles. A mound at the top is characterized by coalescent spheroids possibly made of a keratose sponge fibers mesh.